Reservoir engineering handbook - Ahmed, Tarek H., 1946- (Elsevier/Gulf Professional, 2006)
Reservoir Engineering, Third Edition provides solid information and insight for engineers and students alike on maximizing production from a field in order to obtain the best possible economic return. This guide contains information on predicting oil reservoir performance through the analysis of oil recovery mechanisms and performance calculations. It also contains valuable information on key relationships among the different operating variables. The examples contained within this reference demonstrate the performance of processes under forceful conditions through a wide variety of applications.